Changes in physical development of children at Poznań over the last half century - Żuławski, Waldemar (Anthropological Review, 1974)
The results of comparative evaluation of the physical development of children in Poznań in the years 1922 - 27 with the development of present-day children have been presented. The increase in stature of boys and girls over the years from 1922 to 1969 took place in all the analysed age groups from age 7 to 14. The average increase in stature of boys was from 5.20 cm in boys at 7 up to 7.40 cm in boys at 14. It has been found that the present-day youth in Poznań is taller and more slender in comparison with the youth of older generations.